Cultivating a sense of nationalism through storytelling at SDN Bendomungal II Bangil - Laili, Innayatul; Lestari, Sely Ayu; Saputri, Ernia Duwi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study uses a qualitative approach. The purpose of this study is the application of instilling a sense of nationalism in students through the storytelling learning method. The data collection was carried out using observation, interviews, and documentation. With the object of research being 5th grade students at SDN Bendomungal II Bangil, Pasuruan Regency. The results of this study prove that by using the storytelling method, students' enthusiasm for learning becomes higher. This can be seen through the results of observations and interviews with students. In addition, students' knowledge of heroes in Indonesia is increasing. Students even feel more confident in telling short biographies of the heroes they have previously searched for.